(untitled) (Patan Pragya, 2020)
This paper briefly discusses about the income and generation of employment contributed by the Private Schools in Nepal. The educational system of Nepal includes school education and higher education. In both levels, the role of private education has grown up, promoted and explored by some educational actors as a solution to the lack of sufficient public provision of education or underperforming public schools. Primary source has been used for collection of data. The main purpose of collecting primary data and information at micro level is to understand academic environment, income and employment situation, perception of teachers, and academic facilities with the school of sample schools. There are significant numbers of semi-skilled and unskilled labor force in private schools. Hence school is also providing employment not only to the skilled and educated mass but also to the unskilled and semi-skilled both male and female workers.